Current Dumping Analysis - Malvar, Henrique S.; Malvar, Henrique S. (Wireless World, 1981)
This paper presents an analysis of Walker's "current dumping" technique, which combines feedback and feedforward to significantly reduce nonlinearity distortions in Class B amplifiers. Current dumping is thus a good alternative to Class AB designs, as it avoids biasing circuits that may need careful adjustment and temperature compensation.